Law, crime, and English society, 1660-1830 - Landau, Norma (Cambridge University Press, 2013)
This book examines how eighteenth-century law was made, defined, administered, and used. Leading historians introduce current debates about the nature of eighteenth-century law and society and reflect on contemporary concepts of corruption, oppression, and institutional efficiency. The result is an invaluable account of the legal bases of eighteenth-century society.